Decrease of Markers Related to Bone Erosion in Serum of Patients with Musculoskeletal Disorders after Serial Low-Dose Radon Spa Therapy - Cucu, Aljona; Shreder, Kateryna; Kraft, Daniela; Rühle, Paul Friedrich; Klein, Gerhart; Thiel, Gerhard; Frey, Benjamin; Gaipl, Udo S.; Fournier, Claudia (Frontiers in Immunology, 2017)
Musculoskeletal disorders (MSDs) are the most frequent cause of disability in Europe. For the patients, reduced mobility and quality of life is often associated with pain due to chronic inflammation. The inflammatory process, accompanied by a destruction of the cartilage and bone tissue, is discussed as a result of (A) the infiltration of immune cells into the joints, (B) an altered homeostasis of the joint cavity (synovium) with a critical role of bone remodeling cells and (C) release of inflammatory factors including adipokines in the arthritic joint. In addition to the classical medication also low-dose radiation therapy using photons or radon spa treatments has shown to reduce pain and to improve the mobility of the patients. However, the cellular and molecular mechanisms of anti-inflammatory effects of radon are yet poorly understood. We analyzed blood and serum samples from 32 patients, suffering from MSDs, which had been treated in the radon spa in Bad Steben (Germany). Before and after therapy we measured the levels of markers related to bone metabolism (collagen fragments type-1, cartilage oligomeric matrix protein, receptor activator of NFκB ligand, osteoprotegerin) in the serum of patients. Also, adipokines related to inflammation (visfatin, leptin, resistin and adiponectin) were analyzed. Some of these factors are known to correlate with disease activity. Since T-cells play an important role in the progression of the disease we further analyzed in blood samples the frequency of pro- and anti-inflammatory T cell subpopulations (CD4+IL17+ T cells and CD4+FoxP3+ regulatory T cells). Overall, we found a decrease of collagen fragments (CTX-I), indicating decreased bone resorption, presumably by osteoclasts, in the serum of MSD patients. We also observed reduced levels of visfatin and a consistent trend towards an increase of regulatory T cells in the peripheral blood, both indicating attenuation of inflammation. However, key proteins of bone metabolism were unchanged on a systemic level, suggesting that these factors act locally after radon spa therapy of patients with MSDs.